Recovery of nickel from simulated industrial wastewater via homogeneous phosphate granulation in a fluidized - bed reactor - Baldovia, Jacklyn M.
Nickel is one of the most valuable and commonly used metals in industries. However, wastewater with high concentration of nickel are significantly detrimental to the environment and humans. In this study, efficiency of the homogeneous fluidized-bed granulation process in removing and recovering nickel from simulated industrial wastewater with phosphate as the precipitant was investigated through determining the best operating parameters by varying operating pH and [Ni²?:PO4³¯] ,molar ratio. At optimum experimental condition, the nickel removal and recovery reached 99% and 92%, respectively. The size of recovered solid granules ranged from 0.590 to 1.0 mm. The effects of copper ions (Cu²?) and complexing agents such as sodium hypophosphite, citrate, ammonia and EDTA on nickel recovery and granulation were also evaluated. The results showed that Cu²? and other complexing agents had minimal effect on the removal and removal and recovery of nickel with an order of: EDTA > citrate > hypophosphite > ammonia > Cu²?. Overall, homogeneous phosphate granulation in fluidized-bed reactor was found to be an efficient and a promising process for nickel ion recovery from wastewa